Evaluation of Damage and Strengthening Recommendations: A Case Study of the Lontar Badminton Sports Hall - RIzky T Amalia; Harun Alrasyid (Journal of Civil Engineering, 2026)
An evaluation and recommendations for strengthening the structure of the Lontar Badminton Sports Hall were conducted to assess its adequacy after damage occurred to the strauss piles and the collapse of the retaining wall. Evaluation methods included an initial survey, destructive and non-destructive testing of structural elements, and structural analysis. Material test results indicated that the compressive strength of the concrete in the upper structure averaged 22.55 MPa. In contrast, the strauss pile structure had an average compressive strength of only 6.81 MPa. This disparity suggests that the concrete quality in the substructure elements is substandard. Analysis of the steel element capacity revealed a maximum cross-sectional capacity ratio of 10.7 for the HCO and CNP profiles. This indicates that certain elements may not be able to support the design load. Additionally, five types of pile caps—PC1, PC1-A, PC2, PC4, and PC5—have been identified as unsafe due to a combination of axial loads and moments that exceed their capacity. Furthermore, the reinforced concrete floor slabs are unable to bear the existing loads because of their excessive spanning area. Recommendations for strengthening the upper structure include adding steel elements, specifically WF 200x100 longitudinal beams, and adjusting the profiles to enhance overall structural stiffness and capacity. For the lower structure, proposed modifications involve adjusting the number and dimensions of foundations and pile caps to improve the lower structural configuration